Effects of Natural Disasters on Children and Adolescents - Derya Karabulut; Tolga Bekler (Doğal Afetler ve Çevre Dergisi)
Natural disasters are unpredictable natural phenomena that can result in a large number of life and property losses, with an unknown level of impact. We are witnessing different natural disasters every year in the world and in our country, and the effects of these disasters on communities. Children and adolescent people are the most sensitive and vulnerable individuals when exposed to disasters. Every year, millions of children and young people around the world are exposed and affected by various natural and man-made disasters. This study was conducted to raise awareness of the effects of natural disasters on children and adolescents. Theses and articles obtained by using search words and phrases such as disaster, natural disasters, disaster effects, disasters and children, disasters and young people, child development from different databases such as Yöktez, Google Scholar, Dergi Park, EM-DAT, Science Direct, PubMed, International Journal of Psychiatry and Psychology Studies, International Journal of Family Child and Education, have been reviewed and interpolated as to form a data base for further studies.